Development of a multiplex RT-PCR assay for simultaneous detection of Cucumber green mottle mosaic virus and Acidovorax citrulli in watermelon - Bi,Xinyue; Li,Xiaodong; Yu,Haibo; An,Mengnan; Li,Rui; Xia,Zihao; Wu,Yuanhua (PeerJ, 2019)
Watermelon (Citrullus lanatus Thunb.) is considered as a popular and nutritious fruit crop worldwide. Watermelon blood flesh disease caused by Cucumber green mottle mosaic virus (CGMMV) and bacterial fruit blotch caused by Acidovorax citrulli, are two major quarantine diseases of watermelon and result in considerable losses to global watermelon production. In this study, a multiplex reverse-transcription polymerase chain reaction (RT-PCR) method was developed for simultaneous detection of CGMMV and A. citrulli in both watermelon leaves and seeds. Two pairs of specific primers were designed based on the conserved sequences of the genomic RNA of CGMMV and the internal transcribed spacer of A. citrulli, respectively. Transcriptional elongation factor-1α from watermelon was added as an internal reference gene to prevent false negatives. No cross-reactivity was detected with other viral or bacterial pathogens infecting watermelon. Moreover, the multiplex RT-PCR showed high sensitivity and could simultaneously detect CGMMV and A. citrulli as little as 102 copies of plasmid DNA. This method was successfully applied to test field-collected watermelon leaves and stored seeds of cucurbitaceous crops. These results suggested that the developed multiplex RT-PCR technique is a rapid, efficient, and sensitive method for simultaneous detection of CGMMV and A. citrulli, providing technical support for monitoring, predicting, and preventing these two quarantine diseases. To our knowledge, this is the first report on simultaneous detection of a virus and a bacterium by multiplex RT-PCR in watermelon.
Keywords: Multiplex RT-PCR; Cucumber green mottle mosaic virus; Acidovorax citrulli; Watermelon; Detection